Modeling the Fate of Toluene in a Chamber with Alfalfa Plants: 1. Theory and Modeling Concepts - M. Narayanan; J. C. Tracy; L. C. Davis; L. E. Erickson (Journal of Hazardous Substance Research, 1998)
A model was developed to investigate the fate of organic contaminants in soils in the presence of vegetation. The model has two modules. The first module simulates the soil-water and root-water pressure heads under the influence of water extraction by the roots of growing vegetation. Evapotranspiration due to alfalfa plants is an outflux boundary condition at the soil surface for this model. The distributions for water and air contents and Darcy water flux are obtained from the soil-water pressure heads. The second module simulates the fate of soil constituents in the porous medium using the Darcy water flux. The constituents assumed to be present in vegetated soil were contaminant, biomass, oxygen, and root exudates. A Galerkin finite element method was used to solve the model equations in two dimensions to enable comparison with an experimental system. The domain simulating the experimental chamber was assumed to be comprised of rectangular elements with bilinear shape functions which represented the variations within each element. Convergence to solution for the non-linear equations was accomplished using the Picard iterative algorithm. The time derivative was approximated using an implicit Crank-Nicholson scheme.
Keywords: soil; modeling; toluene; gas diffusion; phytoremediation; finite element model